Convergence of the series of large-deviation probabilities for sums of independent equally distributed random variables - Klesov, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The series $\sum olimits_{n \geqslant 1} {τ _n P(|S_n | \geqslant ε n^a )}$ is studied, where $S_n$ are the sums of independent equally distributed random variables, $τ_n$ is a sequence of nonnegative numbers, $α > 0$, and $ɛ > 0$ is an arbitrary positive number. For a broad class of sequences $τ_n$, the necessary and sufficient conditions are established for the convergence of this series for any $ɛ > 0$.